2020
DOI: 10.3389/fneur.2020.573382
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Blood Pressure After Successful Endovascular Therapy for Anterior Acute Ischemic Stroke: A Systematic Review

Abstract: Background and Purpose: Optimal blood pressure (BP) targets after endovascular therapy (EVT) for acute ischemic stroke (AIS) still need to be assessed, especially according to the recanalization status. Facing the lack of randomized controlled trials addressing this question, we performed a systematic review of studies assessing the post-EVT BP impact on functional outcome and symptomatic intracranial hemorrhage (sICH). Methods: Studies published after January 1, 2012 were included in the systematic review. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Cho et al also demonstrated a negative effect of increased mean SBP and observed an increased influence of these parameters in successfully recanalized patients compared to non-recanalized patients 44 . Two meta-analysis described an association between the variability of the SBP and a poor clinical result 45 , 46 , but no association with the 90-day mortality 46 . Further meta-analyses confirmed a significant association of increased SBP after MT 47 or pre- and post-interventional 9 with a poor clinical result.…”
Section: Discussionmentioning
confidence: 99%
“…Cho et al also demonstrated a negative effect of increased mean SBP and observed an increased influence of these parameters in successfully recanalized patients compared to non-recanalized patients 44 . Two meta-analysis described an association between the variability of the SBP and a poor clinical result 45 , 46 , but no association with the 90-day mortality 46 . Further meta-analyses confirmed a significant association of increased SBP after MT 47 or pre- and post-interventional 9 with a poor clinical result.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal BP parameters after EVT are uncertain; our findings showed that lower BP was favorably associated with functional outcome even among patients with large infarcts. 40 , 41 Whether lowering BP will translate to better outcomes remains unclear. Hyperglycemia occurs in approximately 40% of patients with acute ischemic stroke and is associated with worse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…These include BP control, glucose, and hemoglobin at 24 hours. Optimal BP parameters after EVT are uncertain; our findings showed that lower BP was favorably associated with functional outcome even among patients with large infarcts . Whether lowering BP will translate to better outcomes remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This study provides Class IV evidence that for adults with contrast-enhancing lesions after successful EVT of an AIS, Values are expressed as n/no (%). 1 ORs were calculated using logistic regression models. 2Adjusted using IPTW where the propensity score was calculated with all parameters in Table 1.…”
Section: Classification Of Evidencementioning
confidence: 99%